Induction of Onion (Allium cepa L. cv. Granex 33) Callus Formation and Embryogenesis - Niran Juntawong; Prasart Kaumanee; Malee Nanankorn; Surirat Khewhok (Agriculture and Natural Resources, 1993)
The comparative study on growth and differentiation between basal portion and bulb scale of onion (Allium cepa L cv. Granex 33) grown on different culture media were carried out. The results showed that the basal plate tissue cultured on Murashige and Skoog medium (MS) containing 1.0-1.5 mg/I 2,4-dichlorophenoxy acetic acid (2,4-D) and on modified MS medium containing 3.3 mg/1 3,6-dichloro-o-anisic acid (Dicamba) was remarkedly induced to form a compact callus within 6 weeks after culture initiation. However, embryogenesis has been generated only from the callus mediated directly on MS medium containing 1.0 mg/I 2,4-D and subsequently cultured on MS medium comprising 0.1 mg/1 indole-3-acetic acid (IAA) and 1.0 mg/I 6-benzylaminopurine (BAP) within 15 weeks. After transferring onto MS medium containing no growth regula¬tors the embryoid developed into complete plantlets within 8 weeks. In contrast to the basal portion tissue, the bulb scale tissue cultured on these media produced afriable callus which could not regenerate into complete plantlets.